Chromosomal Damage and Apoptosis in Exfoliated Buccal Cells from Individuals with Oral Cancer - Lavínia Tércia Magalhães Dórea; José Roberto Cardoso Meireles; Júlia Paula Ramos Lessa; Márcio Campos Oliveira; Carlos Alberto de Bragança Pereira; Adriano Polpo de Campos; Eneida de Moraes Macílio Cerqueira (International Journal of Dentistry)
This study aimed to investigate cytological abnormalities indicative of chromosome damage (micronuclei) and apoptosis (karyorrhexis, pyknosis, and condensed chromatin) in exfoliated cells from the buccal mucosa of patients with oral cancer and control subjects. The sample included twenty individuals with oral cancer and forty individuals with normal buccal mucosa. Material was collected from the cheek epithelium in areas with lesions and areas without abnormalities. A minimum of one thousand cells was analyzed. Micronuclei were found significantly more frequently in cells collected from lesions than in cells from normal areas, independent of the presence/absence of cancer (P<0.0001). They were also significantly more frequent in smokers and in mouthwash users (P<0.0001). Apoptosis occurred significantly less frequently in individuals with oral cancer (P<0.0001). These results show that oral cancer is associated with higher frequency of chromosomal damage and suggest that apoptosis is compromised in the buccal cells of individuals with this kind of neoplasia.